1994
DOI: 10.1172/jci117079
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and chromosomal mapping of human aquaporin of collecting duct.

Abstract: We recently cloned a cDNA of the collecting duct apical membrane water channel of rat kidney, which is important for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
85
1
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(99 citation statements)
references
References 36 publications
10
85
1
3
Order By: Relevance
“…5,6) Secreted AVP from the pituitary gland binds to V 2 receptors located in the basolateral membrane of principal cells in the collecting ducts, and then the activated V 2 receptors trigger the transport of AQP2 from intracellular storage vesicles into the apical membrane. The amount of AQP2 activated determines the water permeability in the apical membrane and then dominates urinary concentrating ability.…”
Section: Article P533mentioning
confidence: 99%
“…5,6) Secreted AVP from the pituitary gland binds to V 2 receptors located in the basolateral membrane of principal cells in the collecting ducts, and then the activated V 2 receptors trigger the transport of AQP2 from intracellular storage vesicles into the apical membrane. The amount of AQP2 activated determines the water permeability in the apical membrane and then dominates urinary concentrating ability.…”
Section: Article P533mentioning
confidence: 99%
“…The mechanism for the appearance of NDI symptoms in female carriers is explained by an extremely skewed inactivation of the normal allele of the X chromosome [24]; the frequency of this event was estimated to be very rare [9]. However, a recent study by Sato et al [25] showed that a moderately skewed inactivation of the normal allele is enough to cause NDI symptoms.…”
Section: Frequency Of Symptomatic Carriers Of Avpr2 Mutationsmentioning
confidence: 99%
“…After the cloning of human AQP2 [9] and the first report of an NDI patient with mutated AQP2 [10], we have performed gene mutation analyses of Japanese NDI patients. At the end of July 2012, the total number of analyzed NDI families was 78, a significant number which may provide some insights into the genetic causes of hereditary NDI.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after, the AQP2 gene encoding the vasopressin-regulated water channel aquaporin-2 (AQP2) was cloned [8,9] and in 1994 mutations in AQP2 were found to underlie the rare autosomal forms of DI [10]. The discovery of these key molecules allowed the development of targeted drugs.…”
Section: Introductionmentioning
confidence: 99%